A comparative study between onlay and sublay meshplasty in ventral hernias: a randomized controlled trial - Chitrambalam, Tharun Ganapathy; Anguraj, Preetham; Sundaraj, Jeyakumar; Pethuraj, Manimaran (International Surgery Journal, 2019)
Background: Ventral hernias are one of the most common surgical problems of the modern age. About 15-18% of all the surgical procedures performed around the world comprises of hernia repair. This study aims to compare the two common options of mesh placement in open ventral hernia repairs; over the anterior rectus sheath, the ‘Onlay meshplasty’ and in the retrorectus plane, the ‘Sublay meshplasty’. Methods: A prospective controlled study was done between March 2017 to August 2018 on 150 patients with ventral hernia randomizing patients into 2 groups. Group A (Onlay meshplasty) and Group B (Sublay meshplasty). Duration of surgery, post-operative pain, wound infection, duration of hospital stay and recurrences were analysed with 12 months follow up. Results: The mean duration of surgery in group A was 48.49±0.71 minutes and in group B was 72.84±0.72 minutes. Group B experienced significantly lesser pain when compared with group A. The mean asepsis score in group A was 3.60±1.09 and in group B was 0.47±0.30 with a p value of 0.006. Group A had significantly longer hospital stay (9.39 days) than group B (5.71 days). The recurrences in both the groups were statistically insignificant (Group A- 2 patients; Group B- 1 patient). Conclusions: Sublay meshplasty although requires longer time to perform, proves to be a better alternate in terms of post-operative pain, wound infection and hospital stay.